Pengaruh Ukuran Perusahaan, Leverage dan Tipe Industri terhadap Carbon Emission Disclosure: Studi Empiris Pada Perusahaan Non Industri Jasa yang Terdaftar di BEI Tahun 2018-2020 - Rusdi Rusdi; Nayang Helmayunita (Jurnal Eksplorasi Akuntansi, 2023)
This study aims to determine the effect of company size, leverage and industry type on carbon emission disclosures. To measure the extent of disclosure of carbon emissions by companies in Indonesia, the researcher uses a checklist developed based on the information request sheet provided by the carbon emission disclosure project.This research is a type of causal associative research with the type of data used is quantitative data. The population in this study are non-service industry companies listed on the Indonesia Stock Exchange for three years, from 2018-2020. The sampling method used was purposive sampling method and the samples obtained were 48 samples that met the criteria. The data used are financial statements and company annual reports, research samples obtained from the company's official website and the official website of the Indonesia Stock Exchange (www.idx.co.id). The data analysis technique applied is multiple linear regression analysis. The results showed that partially the size of the company had a positive and significant effect on carbon emission disclosures, leverage had no and insignificant effect on carbon emission disclosures and the type of industry had a positive and significant effect on carbon emission disclosures.